2020
DOI: 10.1016/j.jrp.2020.104042
|View full text |Cite
|
Sign up to set email alerts
|

Trait aggression is primarily a facet of antagonism: Evidence from dominance, latent correlational, and item-level analyses

Abstract: Both authors contributed to the conceptualization of the study, data collection and preparation. DSC analyzed the data and wrote the initial report, SJW provided critical revisions. AcknowledgmentsResearch reported in this publication was supported by the NIAAA under award K01AA026647 (PI: Chester).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
7
16
0
1
Order By: Relevance
“…Others have argued that trait aggression is essentially antagonism (commonly known as low agreeableness), with latent correlations between constructs in the −.67 to −.90 range (Chester & West, 2020).…”
Section: E Viden Ce Of a Con S Truc T Overl Ap Prob Lem And Con S Truc T Prolifer Ation Con Cernsmentioning
confidence: 99%
“…Others have argued that trait aggression is essentially antagonism (commonly known as low agreeableness), with latent correlations between constructs in the −.67 to −.90 range (Chester & West, 2020).…”
Section: E Viden Ce Of a Con S Truc T Overl Ap Prob Lem And Con S Truc T Prolifer Ation Con Cernsmentioning
confidence: 99%
“…Taylor et al (2018), for example, showed that violence occurred after a complex interaction between multiple variables, none of which alone was violent or aggressive. These results, however, do lend support to the trait aggression approaches (Chester & West, 2020). While the focus of the current research was on behavioral analysis, given the large corpus of research focusing on personality factors related to aggression and implicit cognitive processes, it would be possible to suggest links between behaviors and cognitions.…”
Section: Discussionmentioning
confidence: 60%
“…More recent research into aggression has focused dispositional aggression as a predictor across an individual’s lifespan (Chester & West, 2020). Chester and West (2020) highlight that while the Buss-Perry Aggression model (1992) is widely used in the research literature and applied settings, it focuses primarily on cognitive and affective processes, while aggression typically relates to behaviors. Indeed, in an applied setting, it is the behaviors that are in many ways more important to accurately detect, as they may serve as a clearer indicator of aggressive, violent attacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, AAS dependents have demonstrated reduced ability to infer or interpret the mental state of others compared to non-using weight-lifters (66). Furthermore, antagonism and disinhibition may contribute to externalizing behaviors (67,68) which may put others at risk, including sexual aggression (69).…”
Section: Discussionmentioning
confidence: 99%